Influence of uterine flushings from superovulated cows on in vitro bovine morulae development - Toole, R.J.; Gwazdauskas, F.C.; Whittier, W.D.; Vinson, W.E. (Journal of Economic Literature, 1988)
To evaluate early embryo development, 248 good to excellent bovine morulae were cultured in Ham's F-10 medium, supplemented with 10% steer serum, uterine flushings from Days 6, 10 or 15 following estrus (0.01, 0.1, 1.0 and 10% protein; 64 mg protein/ml), and 1.0% uterine flushings and 10% steer serum. Final development scores for embryos in steer serum were significantly higher (range across experiments was: 4.06 to 4.37) than for embryos cultured in uterine flushings alone (-0.23 to 0.52). Treatment means were not different (P >0.05) when 10% steer serum was added to 1.0% uterine flushings. A higher percentage of embryos in 10% steer serum (92%) than in 10% steer serum plus 1.0% uterine flushing from Day 6 (33%), Day 10 (45%) and Day 15 (50%) developed to hatched blastocysts. Embryos cultured in 1.0% Day 6 uterine flushings plus 10% steer serum required more time to attain the early blastocyst and blastocyst stages, while embryos in 1.0% Day 15 uterine flushings and 10% steer serum developed at the same rate as controls to the expanded blastocyst stage, but hatched sooner (72.8 vs 96.5 h). These results suggest substance(s) in uterine secretions can have inhibitory and stimulatory influences on early bovine embryo development.